El Rol de la Tecnología en la Gestión de la Salud en Hospitales Públicos - Palacios Quezada, Gino Adrián (My University, 2025)
Introduction: The management of public hospitals faces growing challenges derived from the aging population, the expansion of chronic diseases, and the pressure on healthcare systems. In this context, technology represents a key tool to optimize processes and improve the quality of care. Objective: To analyze the impact of technology on healthcare management in public hospitals through a systematic review of the scientific literature. Methodology: The PRISMA methodology was applied. A search was conducted in databases such as PubMed, Scopus, Web of Science, and institutional repositories, including studies published between 2020 and 2025. sixteen articles that met specific inclusion criteria were selected and analyzed through qualitative thematic synthesis. Results: The most frequently used technologies were electronic medical records, telemedicine, artificial intelligence, and hospital information systems. The studies reported improvements in operational efficiency, care coordination, and user satisfaction. However, barriers such as low investment and institutional resistance persisted. Conclusions: Technology is a strategic component in the modernization of public hospitals. Its effective implementation depends on inclusive policies, institutional leadership, and financial sustainability
Introducción: La gestión de los hospitales públicos enfrenta desafíos crecientes derivados del envejecimiento poblacional, la expansión de enfermedades crónicas y la presión sobre los sistemas sanitarios. En este contexto, la tecnología representa una herramienta clave para optimizar procesos y mejorar la calidad de atención. Objetivo: Analizar el impacto de la tecnología en la gestión de la salud en hospitales públicos mediante una revisión sistemática de la literatura científica. Metodología: Se aplicó la metodología PRISMA. Se realizó una búsqueda en bases como PubMed, Scopus, Web of Science y repositorios institucionales, incluyendo estudios publicados entre 2020 y 2025. Se seleccionaron 16 artículos que cumplían con criterios de inclusión específicos y fueron analizados mediante síntesis temática cualitativa. Resultados: Las tecnologías más recurrentes fueron historia clínica electrónica, telemedicina, inteligencia artificial y sistemas de información hospitalaria. Los estudios reportaron mejoras en eficiencia operativa, coordinación asistencial y satisfacción del usuario. Sin embargo, persistieron barreras como la escasa inversión, resistencia institucional. Conclusiones: La tecnología es un componente estratégico en la modernización de los hospitales públicos. Su implementación efectiva depende de políticas inclusivas, liderazgo institucional y sostenibilidad financiera.
Keywords: TECNOLOGÍA SANITARIA; GESTIÓN HOSPITALARIA; SALUD DIGITAL; HOSPITALES PÚBLICOS